âMaqashid Al-Shariaâ Perspective for Character Building among Street Children in Makassar, South Sulawesi. - Ipandang, Ipandang (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Negative images to street children have raised attention for all those concerned about the street childrenâs character building. This article discusses three basic problems; the street children reality in Makassar city, fostering and emergence of factors of street children and âmaqashid al-shariaâ principles on character building for the street children in Makassar, South Sulawesi. In the perspective of âmaqashid al-shariaâ, the position of street children clearly has rules and normative legal basis. Fostering childrens character has a fundamental meaning which is the basis of values to change the fate of children, as well as a comprehensive approach to man in spiritual education and noble character. This article meant to emphasize the role of âmaqashid al-shariaâ perspectives in character building; therefore, street children of Makassar will struggle toward a better future.—–Anak jalanan sering mendapat citra negatif, sehingga menjadi fokus perhatian dari semua pihak dalam upaya pembinaan karakter mereka. Artikel ini secara fokus membahas tiga pokok masalah antara lain; realitas anak jalanan Kota Makassar, faktor munculnya dan pembinaannya serta prinsip âmaqashid al-syariahâ dalam pembinaan karakter anak jalanan di Kota Makassar. Dalam perspektif âmaqashid al-syariahâ, kedudukan anak jalanan di Kota Makassar secara jelas memiliki aturan dan landasan hukum normatif.Pembinaan karakter anak memiliki makna yang fundamental yaitu sebagai nilai dasar untuk melakukan perubahan nasib anak, serta sebagai pendekatan komprehensif bagi manusia dalam pendidikan rohani dan kemuliaan karakter. Artikel ini menganalisis perspektif âmaqashid al-syariahâ dalam pembinaan karakter, sehingga anak jalanan di kota Makassar dapat berubah menuju masa depan yang cerah.